Method for extracting lithium from lithium-containing silicate mineral and by-producing porous nano silicon dioxide
A method for extracting lithium from silicate minerals using metal inorganic salts and acid activation under high pressure addresses energy inefficiencies and environmental issues, achieving high lithium extraction rates and producing valuable nano-silica by-products.
Patent Information
- Application Number
- CN202411320702.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Existing lithium extraction methods from lithium-containing silicate minerals are energy-intensive, environmentally unfriendly, and result in large amounts of slag with low resource utilization efficiency, and do not effectively address the treatment of waste residues.
A method involving ball-milling lithium-containing silicate minerals with metal inorganic salts, followed by acid activation under high temperature and pressure, and subsequent pH adjustment to induce crystallization, resulting in the extraction of lithium and production of porous nano-silica as a by-product.
The method achieves high lithium extraction rates with low energy consumption, comprehensive utilization of elements, and avoids environmental pollution by not producing tailings, with the produced nano-silica having high purity and specific surface area suitable for applications in cosmetics, medicine, and coatings.
Smart Images

Figure CN119194108A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium extraction, and in particular to a method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product. Background Art
[0002] Lithium is a lightweight, highly active metal element that is widely used in traditional fields such as batteries, glass and ceramics, petrochemicals, metallurgy, textiles, synthetic rubber, lubricating materials, and medical treatment. It is also a key raw material in emerging fields such as new energy vehicles and energy storage systems. With the global pursuit of clean energy and sustainable development, the demand for lithium is growing, especially in the field of lithium-ion batteries, where the demand for lithium has surged, promoting the development of lithium resources and the advancement of lithium extraction technology.
[0003] Lithium extraction technology from lithium ore can be divided into two categories: lithium extraction from salt lakes and lithium extraction from ores. Lithium extraction from salt lakes uses lithium resources in salt lakes to extract lithium through physical and chemical methods, including precipitation, solar pond, extraction, calcination, adsorption, etc. Lithium extraction technology from ores mainly uses pyrolysis and hydrolysis, which are mainly used to destroy the mineral structure and extract lithium by leaching. Among them, pyrolysis includes limestone method, sulfate method, chloride method, etc., and hydrolysis includes soda pressure leaching method, alkali dissolution method, etc.
[0004] At present, the industrial lithium extraction process is mostly to roast lithium-containing minerals at high temperature, and then add acid, salt roasting or alkali pressure cooking. It generally involves the use of concentrated sulfuric acid, sulfate, fluoride and other agents, which has the characteristics of high energy consumption, environmental unfriendliness, low resource utilization, and large slag volume. In the industrial lithium extraction process, the tailings after lithium extraction are often discarded as "solid waste", but in fact, the slag still contains a large amount of silicon, aluminum and other elements derived from the structure of the lithium ore itself.
[0005] At present, the methods for extracting lithium from lithium mica include sulfate method, high pressure alkali boiling method, sulfuric acid method, chloride method and mechanical activation method. For example, Chinese patent document CN106755967A proposes a method for treating lithium mica by sulfuric acid calcination and preparing lithium carbonate, and the lithium in lithium mica is transformed into soluble lithium sulfate by sulfuric acid roasting; for example, Chinese patent document CN106745097A proposes a method for treating lithium mica by sulfate roasting, and the lithium in lithium mica is transformed into soluble lithium sulfate by high temperature roasting of sulfate; for example, Chinese patent document CN105907943A proposes a method for treating lithium mica by chloride roasting, and the lithium in lithium mica is transformed into soluble lithium chloride by high temperature roasting of chloride; for example, Chinese patent document CN108163874A proposes a method for hydrothermal treatment of lithium mica, and the lithium in lithium mica is transformed into soluble lithium hydroxide by high temperature hydrothermal treatment. Although these methods can effectively extract lithium from lepidolite, they generally have problems such as high energy consumption, large amount of slag and low leaching rate.
[0006] Chinese patent document CN115747520B discloses a method for extracting lithium from lithium-containing ores, comprising the following steps: (1) the lithium-containing ore is subjected to acidification treatment to obtain a lithium-containing acidified liquid; (2) the lithium-containing acidified liquid is subjected to primary filtration treatment, nanofiltration treatment and ion exchange treatment in sequence to obtain a lithium-containing concentrated liquid; the ion exchange resin used in the ion exchange treatment includes a chelating resin with N as a coordinating atom; (3) the lithium-containing concentrated liquid is subjected to sodium removal treatment to obtain a lithium chloride product. However, the lithium yield of multiple embodiments of the patent is only 52.5-88.5%, and because a cation exchange resin is used, when the ion exchange load is high, frequent resin regeneration is required, and the patent does not involve the treatment of waste residue after lithium extraction from lithium-containing ores.
[0007] Chinese patent document CN114350978A discloses a method for extracting lithium from lithium-containing clay in steps, comprising the following steps: S1, mixing uncalcined lithium-containing clay with acid, and reacting and leaching at a pressure of 1.5 MPa;
[0008] S2, the product after the reaction of step S1 is subjected to solid-liquid separation to obtain filtrate and filter residue, and the filter residue is washed; S3, the filter residue after washing in step S2 is mixed with acid, and then reacted and leached at a pressure of 1.5MPa; S4, the product after the reaction of step S3 is subjected to solid-liquid separation to obtain filtrate and filter residue, and then the filtrate is collected. However, the patent involves two stages of high-pressure acid washing, which has high energy consumption, complicated steps, and a general lithium extraction rate, and the subsequent treatment and utilization of the filter residue are not considered. Summary of the invention
[0009] The purpose of the present invention is to provide a method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silica as a by-product, aiming to solve the problems of high energy consumption, environmental unfriendliness, large amount of slag and low resource utilization efficiency in the existing lithium ore extraction process. The method is simple and effective, realizes the comprehensive utilization of resources, and provides a new idea for the high-value utilization of lithium-containing silicate minerals.
[0010] In order to achieve the above object, the present invention provides a method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, the method comprising the following steps:
[0011] (1) mixing a lithium-containing silicate mineral with a first metal inorganic salt, and ball-milling the mixture; wherein the first metal inorganic salt is selected from any one or more of sodium chloride, magnesium chloride, aluminum chloride, calcium chloride, sodium nitrate, magnesium nitrate, calcium nitrate, aluminum nitrate, sodium sulfate and magnesium sulfate;
[0012] (2) subjecting the ball milled product and an acid solution to acid activation under high temperature and pressure conditions, and separating the solid from the liquid to obtain an acid leaching solution and a first solid; washing and drying the first solid to obtain porous nano-silicon dioxide;
[0013] (3) mixing any one or more of a second metal inorganic salt, a metal oxide and a natural mineral with the acid leaching solution, adding the mixture dropwise into water with an alkaline solution, stirring and adjusting the pH, heating and stirring for a period of time, and then aging to induce crystallization of metal ions in the acid leaching solution, and performing solid-liquid separation to obtain a lithium-rich solution and a second solid;
[0014] (4) The second solid is washed with water and dried to obtain a layered double metal hydroxide.
[0015] The method of the present invention mixes a lithium-containing silicate mineral with a metal inorganic salt, and performs acid activation on the mixture under high temperature and pressure conditions. Under such conditions, the use of low concentrations of hydrogen ions can also effectively dissolve the Al, Mg, and Fe metal cations in the octahedron of the lithium-containing silicate mineral. The metal ions contained in the added metal inorganic salt have the effect of promoting the dissolution of the mineral, thereby destroying the structure of the mineral, making the lithium in the mineral easier to dissolve. The metal inorganic salt has the following main functions: (1) acting as a grinding medium, strengthening the destruction of the mineral structure by grinding, and improving the grinding efficiency; (2) hydrated inorganic ions can open the mineral structure from the microcracks on the surface of the mineral and the end faces of the lamellae, causing the lamellae to bulge and produce more cracks, increasing the probability of protons attacking the mineral structure ions, and promoting the dissolution of the mineral; (3) metal ions compete with the dissolved lithium ions for the adsorption sites on the mineral surface, reducing the adsorption of lithium ions; (4) in the process of preparing layered double metal hydroxides, layer plate ions are provided to adjust the crystal form of the layered double metal hydroxide, etc. The first solid obtained by solid-liquid separation after acid activation is washed with water until the pH is neutral and dried to obtain porous nano-silicon dioxide. The acid leaching solution is rich in Al 3+ Mg 2+ , Fe 3+ Add alkali, metal inorganic salt or natural mineral to it. For example, to prepare magnesium aluminum layered double hydroxide, generally add n(Mg 2+ ):n(Al 3+ )=(2~4):1. Too high or too low will affect the crystal form and crystallinity of hydrotalcite. Adjust the pH and supplement metal ions, adjust the molar ratio of metal ions, induce the crystal precipitation of metal ions in the acid leaching solution, and then achieve the purpose of solid-liquid separation. After solid-liquid separation, a lithium-rich acid leaching solution and a second solid are obtained, and then the second solid is washed with water until the pH is neutral and dried. The lithium-rich acid leaching solution contains the first metal inorganic salt and the second metal inorganic salt mentioned above. The salinity will affect the crystallinity, grain size and morphology of the layered double metal hydroxide prepared subsequently. The content of other metal ions except lithium ions in the lithium-rich acid leaching solution is low, which is conducive to the further separation of lithium.
[0016] The first metal inorganic salt used in the present invention contains metal ions that promote mineral dissolution / conversion. For example, Na +After entering the mineral interlayer, it forms expandable sheets, opens the interlayer channels of the structure, and thus promotes the dissolution of the sheet structure; Al 3+ It can not only enter the interlayer of phyllosilicate minerals in the form of ions or polymerized ions, open interlayer channels, and promote the further dissolution of the sheets; it can also participate in the formation of secondary minerals, reduce local ion concentrations, and promote the dissolution of parent mineral elements; and through Al 3+ Hydrolysis provides a large amount of hydrogen ions, lowering the pH of the system, thereby destroying the structure of the mineral. Similarly, Mg 2+ and Ca 2+ Similar effects can be obtained in the system.
[0017] The method of the present invention has a high lithium extraction rate, is simple and efficient, has low energy consumption, and realizes comprehensive utilization of elements. The products include lithium salts, porous nano-silica, and layered double metal hydroxides, which greatly improves economic benefits. In addition, the method does not produce tailings in the whole process, thus avoiding pollution to the environment.
[0018] Preferably, in step (1), the lithium-containing silicate mineral is selected from any one or more of spodumene, petalite, eucryptite, lepidolite, ferrolithium mica, hectorite, lithium kaolinite, lithium illite, hectorite, lithium chlorite, lithium zeolite and jadarite. The lithium-containing silicate mineral used in the present invention is abundant in reserves and low in cost.
[0019] Preferably, in step (1), the mass ratio of the lithium-containing silicate mineral to the first metal inorganic salt is 1:(0.1-10).
[0020] Preferably, in step (1), the ball milling speed is 300 to 900 rpm and the time is 1 to 10 hours.
[0021] Preferably, in step (2), the acid solution is selected from any one or more of hydrochloric acid, nitric acid, phosphoric acid, formic acid, acetic acid and oxalic acid; and the concentration of the acid solution is at least 0.01 mol / L.
[0022] Preferably, in step (2), the high temperature and pressurization conditions are a temperature of 60 to 240° C., a pressure of 0.2 to 2.0 MPa, a filling rate of the container of 10 to 80%, and a time of 2 to 48 hours.
[0023] Preferably, in step (2), the high temperature and pressurization conditions are a temperature of 130 to 180° C., a pressure of 0.2 to 2.0 MPa, a filling rate of the container of 30 to 70%, and a time of 16 to 24 hours.
[0024] Preferably, in step (2), the drying temperature of the first solid is 60-120°C.
[0025] More preferably, in step (2), the drying temperature of the first solid is 70-100°C.
[0026] Preferably, in step (3), the second metal inorganic salt is selected from any one or more of magnesium nitrate, zinc nitrate, aluminum nitrate, iron nitrate, calcium nitrate, chromium nitrate, lanthanum nitrate, magnesium chloride, iron chloride, aluminum chloride, calcium chloride, sodium carbonate, sodium bicarbonate, sodium sulfate, magnesium sulfate, iron sulfate and aluminum sulfate; or / and, the alkali solution, the alkali is selected from metal hydroxide; or / and, the natural mineral is selected from at least one of dolomite, limestone, magnesite and calcite; or / and, the pH is 7 to 13.
[0027] More preferably, in step (3), the alkali solution is selected from any one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, cobalt hydroxide and barium hydroxide.
[0028] Preferably, in step (3), the temperature is raised to 60-150° C. for 2-3 h during the heating and stirring; or / and the aging is performed at a temperature of 75-120° C. for 2-18 h.
[0029] More preferably, in step (3), the heating and stirring is performed at a temperature of 75 to 120° C. for 2 to 3 hours.
[0030] The method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product has the following advantages:
[0031] (1) The present invention uses acid to activate lithium-containing silicate minerals. During the process, a large amount of insoluble substances will not be generated. Elements such as lithium, magnesium, aluminum, and iron are dissolved in hydrochloric acid and enter the solution, and the remaining solid is porous nano-silicon dioxide. By inducing the crystallization and separation of metal ions, metal elements such as magnesium and aluminum are precipitated to prepare layered double metal hydroxides, and the remaining liquid is a lithium-rich solution. This method is used to achieve the comprehensive extraction of lithium, silicon, aluminum and other elements in lithium ore, and the economic benefits are greatly improved;
[0032] (2) The metal inorganic salts used in the present invention have the following main functions: ① acting as grinding media, strengthening the destruction of the mineral structure by grinding, and improving the grinding efficiency; ② hydrated inorganic ions can open the mineral structure from the microcracks on the surface of the mineral and the end faces of the lamellae, causing the lamellae to bulge and produce more cracks, increasing the probability of protons attacking the mineral structure ions, and promoting mineral dissolution; ③ metal ions compete with dissolved lithium ions for adsorption sites on the surface of the mineral, reducing the adsorption of lithium ions; ④ in the process of preparing layered double metal hydroxides, providing layer plate ions, adjusting the crystal form of the layered double metal hydroxides, etc. Since it can provide different metal ions as layer plate ions, it can be used to prepare layered double metal hydroxides with various properties and different uses. The lithium-containing silicate minerals used in the present invention are rich in reserves, low in cost, high in lithium extraction rate, simple and efficient in method, low in energy consumption, and realize the comprehensive utilization of elements. The products include lithium salts, porous nano-silicon dioxide, and layered double metal hydroxides, which greatly improve the economic benefits, and the whole process of the method does not produce tailings, avoiding pollution to the environment.
[0033] (3) The method of the present invention realizes the extraction of lithium from lithium-containing silicate minerals, while leaching out other metal elements in the minerals, and using induced metal ion crystallization to separate lithium from other metal ions. The obtained porous nano-silica has high purity, small particle size, large specific surface area, and high activity, and can be used in the fields of cosmetics, medicine, coatings, etc. The obtained layered double metal hydroxide can be used in the fields of catalysis, medicine, and adsorption. The method has a high lithium extraction rate, is simple and effective, and is environmentally friendly, and can extract and fully utilize the elements contained in lithium-containing silicate minerals. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of the method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product.
[0035] Figure 2 It is the lithium extraction rate of the leaching solution of Example 1 and Example 2 of the present invention.
[0036] Figure 3 It is the Mg / Li of the leachate of Example 1 and Example 2 of the present invention.
[0037] Figure 4 This is the X-ray diffraction pattern of the porous nano-silica obtained in Example 1 of the present invention.
[0038] Figure 5 This is a SEM picture of the porous nano-silica obtained in Example 1 of the present invention.
[0039] Figure 6 This is a TEM image of the porous nano-silica obtained in Example 1 of the present invention.
[0040] Figure 7These are the nitrogen adsorption-desorption curves of the porous nano-silica obtained in Example 1 and Comparative Example 3 of the present invention.
[0041] Figure 8 This is a TEM image of the magnesium-aluminum layered double hydroxide obtained in Example 1 of the present invention.
[0042] Fig. 9 This is the X-ray diffraction pattern of the magnesium-aluminum layered double hydroxide obtained in Comparative Example 2 of the present invention.
[0043] Fig.10 This is the X-ray diffraction pattern of the magnesium-aluminum layered double hydroxide obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.
[0046] Example 1
[0047] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0048] (1) 20 g of lepidolite and 20 g of sodium chloride were added to an agate ball mill, with the mass ratio of agate ball to lepidolite being 10:1, and the milling was performed at 350 rpm for 2 h, and then the mixed powder of lepidolite and sodium chloride was collected;
[0049] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of lithium mica and sodium chloride) is transferred to a 1L polytetrafluoroethylene tank, 400mL of hydrochloric acid with a mass concentration of 18wt.% (6mol / L) is added, and after stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 0.6MPa and a packing rate of 40%. The reactor is transferred to an oven and heated to 180°C for 2 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 60°C to obtain porous nano-silica;
[0050] (3) Collect the acid leaching solution obtained in step (2), add 3.6786g MgO and 8.9206g dolomite to the acid leaching solution, prepare another 400mL alkali solution containing 1.9008mol NaOH and 0.3802mol Na2CO3, and add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 268mL ultrapure water through a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 9 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 75°C, keep stirring for 3 hours, and then continue aging at 90°C in a drying oven for 18 hours;
[0051] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain a magnesium-aluminum layered double hydroxide. The separated liquid is a lithium-rich solution.
[0052] The lithium extraction rate of this embodiment is 92.93%, the magnesium-lithium ratio of the lithium-rich solution is 0.30, and the specific surface area of the obtained porous nano-silica is 142.6 m 2 / g.
[0053] Example 2
[0054] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0055] (1) 25 g of lepidolite and 5 g of sodium chloride were added to an agate ball mill, with the mass ratio of agate ball to lepidolite being 10:1, and the milling was performed at 350 rpm for 2 h, and then the lepidolite powder was collected;
[0056] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of lithium mica and sodium chloride) is transferred to a 500 mL polytetrafluoroethylene tank, 250 mL of sulfuric acid with a molar concentration of 6 mol / L is added, and after stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 1.0 MPa and a filling rate of 50%. The reactor is transferred to an oven and heated to 150° C. for 24 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 120° C. to obtain porous nano-silica;
[0057] (3) Collect the acid leaching solution obtained in step (2), add 22.6660g MgSO4·7H2O to the acid leaching solution, prepare another 250mL alkali solution containing 2.3760mol NaOH, and add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 167.5mL ultrapure water through a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 8 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 75°C, keep stirring for 3 hours, and then continue aging at 90°C in a drying oven for 18 hours;
[0058] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain a magnesium-aluminum layered double hydroxide. The separated liquid is a lithium-rich solution.
[0059] The lithium extraction rate of this embodiment is 88.01%, the magnesium-lithium ratio of the lithium-rich solution is 0.32, and the specific surface area of the obtained porous nano-silica is 162.5 m 2 / g.
[0060] Example 3
[0061] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0062] (1) 25 g of spodumene (calcined at 1100° C. to transform into β-spodumene) and 25 g of anhydrous magnesium chloride were added to an agate ball mill, with the mass ratio of agate ball to spodumene being 10:1, and the milling was performed at 400 rpm for 3 h, and then the spodumene powder was collected;
[0063] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of spodumene and anhydrous magnesium chloride) is transferred to a 500 mL polytetrafluoroethylene tank, 180 mL of sulfuric acid with a molar concentration of 6 mol / L and 70 mL of oxalic acid with a mass concentration of 50% are added, and after stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 2.0 MPa and a packing rate of 50%. The reactor is transferred to an oven, heated to 180°C and kept warm for 48 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 80°C to obtain porous nano-silica;
[0064] (3) Collect the acid leaching solution obtained in step (2), prepare another 150mL alkali solution containing 1.4256mol NaOH and 0.2851mol Na2CO3, and add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 100.5mL ultrapure water by using a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 10 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 90°C, keep stirring for 2 hours, and then continue aging at 120°C in a drying oven for 16 hours;
[0065] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain a magnesium-aluminum layered double hydroxide. The separated liquid is a lithium-rich solution.
[0066] The lithium extraction rate of this embodiment is 92.71%, the magnesium-lithium ratio of the lithium-rich solution is 0.21, and the specific surface area of the obtained porous nano-silica is 85.4 m 2 / g.
[0067] Example 4
[0068] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0069] (1) 40 g of hectorite and 10 g of sodium chloride were added to an agate ball mill, with the mass ratio of agate ball to hectorite being 5:1, and the milling was carried out at a speed of 300 rpm for 2 h, and then the hectorite powder was collected;
[0070] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of hectorite and sodium chloride) is transferred to a 500 mL polytetrafluoroethylene tank, 160 mL of hydrochloric acid with a molar concentration of 5 mol / L and 40 mL of acetic acid with a mass concentration of 30% are added, and after stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 0.2 MPa and a packing rate of 40%. The reactor is transferred to an oven, heated to 130° C. and kept warm for 16 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 100° C. to obtain porous nano-silica;
[0071] (3) Collect the acid leaching solution obtained in step (2), add 35.37g Mg(NO3)2·6H2O and 9.6445gAl(NO3)3 to the acid leaching solution, prepare another 200mL alkali solution containing 1.9008mol NaOH and 0.3801mol Na2CO3, add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 135mL ultrapure water through a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 11 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 70°C, keep stirring for 3 hours, and then continue aging at 90°C in a drying oven for 12 hours;
[0072] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain a magnesium-aluminum layered double hydroxide. The separated liquid is a lithium-rich solution.
[0073] The lithium extraction rate of this embodiment is 89.26%, the magnesium-lithium ratio of the lithium-rich solution is 0.69, and the specific surface area of the obtained porous nano-silica is 411.8 m 2 / g.
[0074] Example 5
[0075] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0076] (1) 20 g of hectorite and 10 g of calcium chloride were added to an agate ball mill, with the mass ratio of agate ball to hectorite being 10:1, and the milling was performed at 300 rpm for 2 h, and then the lithium illite powder was collected;
[0077] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of hectorite and calcium chloride) is transferred to a 500mL polytetrafluoroethylene tank, and 150mL of hydrochloric acid with a molar concentration of 5mol / L and 50mL of formic acid with a mass concentration of 20% are added. After stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 0.6MPa and a packing rate of 40%. The reactor is transferred to an oven and heated to 150°C for 12 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 90°C to obtain porous nano-silica;
[0078] (3) Collect the acid leaching solution obtained in step (2), add 15.7600g limestone to the acid leaching solution, prepare another 200mL alkali solution containing 2.2810mol NaOH and 0.4562mol Na2CO3, and add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 135mL ultrapure water through a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 10 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 70°C, keep stirring for 3 hours, and then continue aging at 75°C in a drying oven for 12 hours;
[0079] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain calcium aluminum layered double hydroxide. The separated liquid is the lithium-rich solution.
[0080] The lithium extraction rate of this embodiment is 90.29%, the magnesium-lithium ratio of the lithium-rich solution is 0.81, and the specific surface area of the obtained porous nano-silica is 167.8 m 2 / g.
[0081] Example 6
[0082] A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, comprising the following steps:
[0083] (1) 20 g of lithium zeolite and 20 g of calcium chloride were added to an agate ball mill, with the mass ratio of agate ball to lithium zeolite being 10:1, and the ball mill was performed at 350 rpm for 5 h, and then the lithium zeolite powder was collected;
[0084] (2) The ball-milled product obtained in step (1) (i.e., the mixed powder of lithium zeolite and calcium chloride) is transferred to a 500 mL polytetrafluoroethylene tank, and 250 mL of hydrochloric acid with a molar concentration of 0.01 mol / L and 50 mL of formic acid with a mass concentration of 20% are added. After stirring, the polytetrafluoroethylene tank is placed in a stainless steel pressure-resistant reactor with a pressure of 1.2 MPa and a packing rate of 60%. The reactor is transferred to an oven and heated to 180°C for 8 hours. After cooling, the solid-liquid mixture in the polytetrafluoroethylene tank is taken out and filtered, and the solid is washed with water and dried at 80°C to obtain porous nano-silica;
[0085] (3) Collect the acid leaching solution obtained in step (2), add 12.0400g of magnesite to the acid leaching solution, prepare another 300mL of alkali solution containing 1.1841mol NaOH and 0.2652mol Na2CO3, and add the acid leaching solution and alkali solution drop by drop into the same beaker pre-filled with 135mL ultrapure water through a pH automatic liquid adding machine at room temperature, and maintain vigorous mechanical stirring and constant pH (pH = 10 ± 0.2). After the addition is completed, transfer the beaker to a water bath and heat it to 70°C, keep stirring for 3 hours, and then continue aging at 75°C in a drying oven for 12 hours;
[0086] (4) After aging, the solid-liquid mixture in the beaker is centrifuged and washed with water for multiple times until the pH of the supernatant is close to neutral, and then separated and dried to obtain calcium aluminum layered double hydroxide. The separated liquid is the lithium-rich solution.
[0087] The lithium extraction rate of this embodiment is 90.29%, the magnesium-lithium ratio of the lithium-rich solution is 0.31, and the specific surface area of the obtained porous nano-silica is 224.7 m 2 / g.
[0088] Comparative Example 1
[0089] The molar concentration of hydrochloric acid in step (2) of Example 1 was changed to 0.001 mol / L, and the rest was the same as Example 1. The lithium extraction rate of this comparative example was 62.71%, the magnesium-lithium ratio of the lithium-rich solution was 16.78, and the specific surface area of the obtained porous nano-silica was 42.72 m 2 / g.
[0090] Comparative Example 2
[0091] The sodium chloride in step (1) of Example 1 was increased from 20 g to 40 g, and the rest was the same as Example 1. The lithium extraction rate of this comparative example was 93.65%, the magnesium-lithium ratio of the lithium-rich solution was 0.42, and the specific surface area of the obtained porous nano-silica was 167.8 m 2 / g.
[0092] Comparative Example 3
[0093] The sodium chloride in step (1) of Example 1 was removed, and the solution was directly subjected to pressure pickling, and the rest was the same as in Example 1. The lithium extraction rate of this comparative example was 85.54%, the magnesium-lithium ratio of the lithium-rich solution was 0.73, and the specific surface area of the obtained porous nano-silica was 62.57 m 2 / g.
[0094] Comparative Example 4
[0095] The sodium chloride in step (1) of Example 6 was removed, and the solution was directly pressurized and pickled at a low acid concentration, and the rest was the same as in Example 6. The lithium extraction rate of this comparative example was 77.52%, the magnesium-lithium ratio of the lithium-rich solution was 0.21, and the specific surface area of the obtained porous nano-silica was 55.48 m 2 / g.
[0096] Table 1 shows the composition of porous nano-silica obtained in various embodiments and comparative examples of the present invention.
[0097]
[0098]
[0099] Note: “-” indicates not detected.
[0100] As shown in Table 1, the proportion of each material component of the porous nano-silica obtained in each embodiment of the present invention. Comprehensively considering the embodiments and comparative examples, when the acid treatment time is the same, the lower the acid concentration used, the lower the purity of the porous nano-silica obtained; when the acid concentration and the acid treatment time are the same, the addition of metal inorganic salts can promote the dissolution of minerals and increase the specific surface area of porous silica; at low acid concentrations (0.1 mol / L), the effect of inorganic salts in promoting mineral dissolution is more obvious, and the pores of silica obtained by the system without adding inorganic salts are underdeveloped. In addition, inorganic / organic composite acids can enhance the effect of acid treatment.
[0101] like Figure 2 As shown, the lithium extraction rate of the leaching solution of Example 1 and Example 2 of the present invention is shown. When hydrochloric acid and sulfuric acid are used for pressurized acid leaching, the lithium extraction rate can reach about 90%.
[0102] like Figure 3 As shown, the Mg / Li of the leaching solution of Example 1 and Example 2 of the present invention, at this time, the Mg / Li of the acid leaching solution is extremely low, only 0.30, which is conducive to the further separation of lithium and other elements.
[0103] like Figure 4 As shown, it is the X-ray diffraction spectrum of the porous nano-silica obtained in Example 1 of the present invention. The phases of the product of pressurized acid leaching of lithium mica include amorphous silicon dioxide and quartz.
[0104] like Figure 5 , which is a SEM picture of the porous nano-silica obtained in Example 1 of the present invention. The obtained porous nano-silica particles are formed by agglomeration of nano-particles, and the particle size is relatively uniform.
[0105] like Figure 6 As shown, it is a TEM picture of the porous nano-silica obtained in Example 1 of the present invention. The porous nano-silica particles obtained are extremely small, only tens of nanometers, and have a rich pore structure.
[0106] like Figure 7 As shown, it is a nitrogen adsorption / desorption curve diagram of the silicon dioxide obtained in Example 1 of the present invention and Comparative Example 3. It can be seen that when other conditions are the same, the mineral dissolution of the system with the addition of metal inorganic salts is more efficient, and has a positive effect on the formation of the multi-level pore structure of silicon dioxide and the increase of specific surface area.
[0107] like Figure 8 , which is the X-ray diffraction pattern of the magnesium-aluminum layered double metal hydroxide obtained in Example 1 of the present invention. The characteristic diffraction peak of the magnesium-aluminum layered double metal hydroxide is relatively strong, indicating that its crystallization is relatively good.
[0108] like Fig. 9 Shown is a TEM image of the magnesium aluminum layered double hydroxide obtained in Example 1 of the present invention.
[0109] like Fig.10 As shown, it is the X-ray diffraction pattern of the magnesium aluminum layered double hydroxide obtained in Comparative Example 2 of the present invention. When the salt concentration increases, the crystallinity of the magnesium aluminum layered double hydroxide becomes significantly weaker, indicating that its grain growth is inhibited to a certain extent.
[0110] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for extracting lithium from lithium-containing silicate minerals and producing porous nano-silicon dioxide as a by-product, characterized in that: The method comprises the following steps: (1) mixing a lithium-containing silicate mineral with a first metal inorganic salt, and ball-milling the mixture; wherein the first metal inorganic salt is selected from any one or more of sodium chloride, magnesium chloride, aluminum chloride, calcium chloride, sodium nitrate, magnesium nitrate, calcium nitrate, aluminum nitrate, sodium sulfate and magnesium sulfate; (2) subjecting the ball milled product and an acid solution to acid activation under high temperature and pressure conditions, and separating the solid from the liquid to obtain an acid leaching solution and a first solid; washing and drying the first solid to obtain porous nano-silicon dioxide; (3) mixing any one or more of a second metal inorganic salt, a metal oxide and a natural mineral with the acid leaching solution, adding the mixture dropwise into water together with the alkaline solution, stirring and adjusting the pH, heating and stirring for a period of time, and then aging to induce crystallization of metal ions in the acid leaching solution, and performing solid-liquid separation to obtain a lithium-rich solution and a second solid; (4) The second solid is washed with water and dried to obtain a layered double metal hydroxide.
2. The method according to claim 1, characterized in that In step (1), the lithium-containing silicate mineral is selected from any one or more of spodumene, petalite, eucryptite, lithium mica, iron lithium mica, hectorite, lithium kaolinite, lithium illite, hectorite, lithium chlorite, lithium zeolite and jaddarite.
3. The method according to claim 1, characterized in that In step (1), the mass ratio of the lithium-containing silicate mineral to the first metal inorganic salt is 1:(0.1-10).
4. The method according to claim 1, characterized in that: In step (1), the rotation speed of the ball mill is 300 to 900 rpm, and the time is 1 to 10 hours.
5. The method according to claim 1, characterized in that In step (2), the acid solution is selected from any one or more of hydrochloric acid, nitric acid, phosphoric acid, formic acid, acetic acid and oxalic acid; and the concentration of the acid solution is at least 0.01 mol / L.
6. The method according to claim 1, characterized in that In step (2), the high temperature and pressurization conditions are a temperature of 60 to 240° C., a pressure of 0.2 to 2.0 MPa, a filling rate of the container of 10 to 80%, and a time of 2 to 48 hours.
7. The method according to claim 1, characterized in that In step (2), the drying temperature of the first solid is 60-120°C.
8. The method according to claim 1, characterized in that In step (3), the second metal inorganic salt is selected from any one or more of magnesium nitrate, zinc nitrate, aluminum nitrate, iron nitrate, calcium nitrate, chromium nitrate, lanthanum nitrate, magnesium chloride, iron chloride, aluminum chloride, calcium chloride, sodium carbonate, sodium bicarbonate, sodium sulfate, magnesium sulfate, iron sulfate and aluminum sulfate; or / and, the alkaline solution, the alkali being selected from metal hydroxides; Or / and, the natural mineral is at least one selected from dolomite, limestone, magnesite and calcite; Or / and, the pH is 7-13.
9. The method according to claim 8, characterized in that In step (3), the alkali solution is selected from any one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, cobalt hydroxide and barium hydroxide.
10. The method according to claim 1, characterized in that In step (3), the temperature is raised to 60-150° C. with stirring for 2-3 hours; Or / and, the aging temperature is 75-120° C. and the time is 2-18 hours.
Citation Information
Patent Citations
A process of extracting lithium from lithium ore through calcination with a chloridizing agent and an inorganic base and dissolving out with an organic solvent
CN105907943A
Method for extracting lithium from lepidolite concentrate
CN106745097A
Method for lepidolite calcination treatment through vitriol and lithium carbonate preparation
CN106755967A
High temperature lepidolite hydrothermal treatment method for producing lithium hydroxide
CN108163874A
Method for extracting lithium from lithium-containing clay step by step
CN114350978A
